Ciphercrypt-an Encryption System / Nor Hidayah Ngah - Nor Hidayah, Ngah (2004)
Ciphercrypt is a stand-alone stem focused 011 providing basic introduction and idea of cryptography implementation to people who are without knowledge and not very familiar with the art of cryptography. This system is implemented on a Windows platform with Visual Basic as a programming language and 3-DES as a main encryption algorithm. By using Ciphercrypt, users can encrypt and decrypt their data as they wanted by simply clicking the encrypt I decrypt button. There arc 3 types of encryption algorithm provided which are 3-DES , RC 4 and RC2. Users need to input any keyword and choose any of the 4 types of keyword hash function which are MD5, MD4, MD2 and SHA-1. Different keyword used will produce a different encrypted / decrypted output. The hashed keyword will be used in encrypt / decrypt process by using any of 3 encryption algorithm mentioned before. The decrypted / encrypted message can be view in Window Notepad and both of the file are automatically created after the encrypt / decrypt proccess. It is hoped that this system will be further developed in the future to explore more functionalities with added enhancements and widen the target group scope.